Analisis Tekanan Sosial Terhadap Keluarga Tanpa Anak Laki-Laki dalam Tradisi Keturunan Suku Karo di Kabupaten Deli Serdang - Apri wahyuni Br Sinulingga; Sudirman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The objective of this research is to analyse the social pressures experienced by families without sons in the tradition of descendants of the Karo Tribe in Deli Serdang Regency. The qualitative descriptive method was employed in this research to accurately describe complex social phenomena through in-depth observations and interviews with respondents who are directly involved in the tradition. The findings indicate that this social pressure emanates from two principal sources: the family and the community. The pressure from the family is frequently manifested in the form of encouragement to give birth again, particularly from the nuclear family. This can create high expectations and potentially undermine the husband-wife relationship, as well as damaging the relationship between husband and wife. Meanwhile, social pressure is exerted in the form of expectations regarding the presence of a son and comments that create a psychological burden. The social pressures faced by families without sons in Karo society reflect deep-seated cultural norms and significantly impact emotional well-being and family dynamics.